Vertical Gaze Palsy in Medial Thalamic Infarction Associated with Vein of Galen Malformation: A Case Report - Sebastian, Leve Joseph; Mishra, Biswamohan; Vibha, Deepti; Nayak, Manoj Kumar (Asian Journal of Neurosurgery, 2025)
The thalamus, a gray matter structure, is a crucial relay for various afferent and efferent pathways in the brain. It receives its primary blood supply from the thalamoperforating and thalamogeniculate branches of the posterior cerebral arteries. Damage to the thalamus can lead to classical sensorimotor and amnestic syndromes, as well as neuro-ophthalmological manifestations, including vertical gaze palsy (VGP), pseudo-abducens palsy, skew deviation, cerebral ptosis, and Horner's syndrome. While most cases of VGP are self-limiting, some can persist, significantly affecting daily life. This report describes a case involving a 33-year-old man with a vein of Galen malformation who underwent embolization and subsequently developed VGP in the postoperative period. This complication was attributed to a medial thalamic infarct. Notably, the patient experienced spontaneous resolution of the gaze palsy within 3 months.
Keywords: thalamic infarct; vertical gaze palsy; vein of Galen malformation; horizontal gaze; syndromes